2006
DOI: 10.1038/sj.jcbfm.9600279
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Affects Cerebral Blood Flow in Humans

Abstract: Mobile phones create a radio-frequency electromagnetic field (EMF) around them when in use, the effects of which on brain physiology in humans are not well known. We studied the effects of a commercial mobile phone on regional cerebral blood flow (rCBF) in healthy humans using positron emission tomography (PET) imaging. Positron emission tomography data was acquired using a double-blind, counterbalanced study design with 12 male subjects performing a computer-controlled verbal working memory task (letter 1-bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
1
6

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 29 publications
6
92
1
6
Order By: Relevance
“…fNIRS during exposure to mobile phones G Curcio et al These findings support the notion that an acute 40-mins exposure to a GSM signal emitted by a commercially available MP affects the frontal hemodynamics, as indexed by fNIRS. This result extends the PET data showing a metabolic increase over the anterior regions (Aalto et al, 2006;Huber et al, 2002Huber et al, , 2005, and provides a physiologic substratum to the attentional improvements observed under GSM irradiation (e.g., Koivisto et al, 2000;Curcio et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…fNIRS during exposure to mobile phones G Curcio et al These findings support the notion that an acute 40-mins exposure to a GSM signal emitted by a commercially available MP affects the frontal hemodynamics, as indexed by fNIRS. This result extends the PET data showing a metabolic increase over the anterior regions (Aalto et al, 2006;Huber et al, 2002Huber et al, , 2005, and provides a physiologic substratum to the attentional improvements observed under GSM irradiation (e.g., Koivisto et al, 2000;Curcio et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…Conversely, if changes in [HHb] concentration mainly reflect variations in oxygen supply, it will be positively correlated with local activation. According to this second hypothesis, the observed increase in [HHb] as a function of MP exposure may be interpreted as a local activation, coherent with the PET studies (Aalto et al, 2006;Huber et al, 2002Huber et al, , 2005.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In addition, a 10-minute interval between phone exposure and subsequent scanning makes the relationship between exposure and CBF responses questionable. In contrast, Aalto et al (2006) Here, we measured relative cerebral metabolic rate of glucose (CMRglu) to trace brain activation (Chang et al, 1987). Cerebral metabolic rate of glucose and CBF are closely coupled (Fox et al, 1988) but represent different physiological processes: CMRglu is a more direct marker of neural activity than CBF.…”
Section: Introductionmentioning
confidence: 99%